Bio-Entrepreneurship and Blue Bio-economy as a Panacea for Achieving Sustainable Development Goal 1 - SULAIMAN, Musa Mohammed (Ilorin Journal of Education, 2025)
Nigeria as a nation is currently experiencing an economic downturn as a result of high level of insecurity, geometric increase in prices of goods and services, and removal of fuel subsidy. This has led to high cost of living, and further increases the number of the populace below the poverty line. In order to increase the economic power of the nation, there is the need to embrace bio-entrepreneurship and by harnessing opportunities in development of blue bioeconomy. This paper discusses the importance of incorporating the concepts of bio-entrepreneurship and blue bioeconomy into the curriculum. It also delves into the various types of bio-entrepreneurship and blue bioeconomy opportunities that could be explored by the populace. The paper further highlights how bio-entrepreneurship and blue bioeconomy can be promoted among the teaming number of unemployed youths. The challenges and possible opportunities as well as the potential bio-entrepreneurs and blue bioeconomist can provide were also discussed. The paper concluded by establishing that, provision of supportive policies by the government can increase the adoption of bio-entrepreneurship and blue-economy principles to alleviate poverty and assist in accomplishing sustainable development goals.